Giant permittivity and dynamic mobility observed for spherical polyelectrolyte brushes - Jiménez, Maria Luisa; Delgado, Angel; Ahualli, Silvia; Hoffmann, Marius; Wittemann, Alexander; Ballauff, Matthias (My University, 2011)
We prcsent a study of the electrodynamic behavior of concentrated suspensions of spherical polyelectrolyte brushcs (SPBs). The dynamic mobility of the SPBs exhibits giant values. Concomitantly, . the dielectric spectra of suspensions of these particlcs display enormous loss peaks in the kHz frequency range. The strong dielectric relaxation is a direct consequence of the inhomogeneity of the counterion distribution inside the polyelectrolyte layer. As can be concluded from the experimentally determined relaxation frequency, the mobility of mono valent counterions is strongly diminished in the brush region. The dynamic behavior ofthe SPBs at high volume fractions can be explained by the assumption that the polyelectrolyte chains deform when particlcs approach each other.
Keywords: 540